Fairy Story Integration for Meaningful Classroom - Muhammad Nur Wangid; Ali Mustadi; Agnestasia Ramadhani Putri (LPMPP Universitas Negeri Yogyakarta, 2018)
Abstract: The National Indonesian Ministry of Education expresses the importance of educating friendliness by stating it in a Master Plan of National Character Development for 2010-2015. However the success of character education needs a meaningful classroom situation. Unfortunately, teaching materials to create meaningful classroom situation that enhances friendliness character is still rare. Sainsmatika fairytale books are science and mathematic’s teaching material which was developed with the wisdom of fairytale, which is attractive to integrate friendliness value. The study aimed to investigate the effectiveness of sainsmatika fairytale books as a means of integrating friendliness into teaching materials for fourth-grade students in Indonesia. A pretest-posttest control-group experimental design was used in this study to investigate the product effectiveness. This study involved 80 fourth-grade students at one of the districts in Indonesia. The experimental group was taught using sainsmatika fairytale books containing one of the character values in character education, i.e., friendliness. The quantitative data were collected through observation on student activity. The data were then analyzed using statistical methods to calculate the values and determine the frequency as well as the mean of pretest and posttest scores in both control and experimental groups. Through one way ANOVA statistical analysis, it was found that the use of sainsmatika fairytale books is significantly effective to enhance the student friendliness.Kata Kunci: fairy stories, sainsmatika, friendliness character Integrasi Cerita Dongeng untuk Pembelajaran BermaknaAbstrak: Kementerian Pendidikan Nasional Indonesia mengekspresikan pentingnya mengajarkan karakter bersahabat dengan memasukkannya ke dalam Master Plan Pengembangan Karakter Nasional 2010-2015. Keberhasilan pendidikan karakter mebutuhkan situasi pembelajaran yang bermakna. Bahan ajar untuk menciptakan situasi pembelajaran bermakna yang dapat meningkatkan karakter bersahabat masih kurang. Buku dongeng sainsmatika adalah bahan ajar sains dan matematika yang dikembangkan dengan pendekatan kearifan dongeng yang menarik untuk diintegrasikan dengan nilai karakter bersahabat. Penelitian ini bertujuan untuk untuk mengetahui keefektifan buku dongeng sainsmatika sebagai bahan ajar terhadap karakter bersahabat siswa. Penelitian menggunakan pendekatan experimental pretest-posttest control-group design. Sebanyak 80 siswa kelas 4 sekolah dasar di salah satu provinsi di Indonesia dilibatkan dalam penelitian ini. Setiap kelas eksperimen belajar menggunakan buku dongeng sainsmatika. Data dikumpulkan dengan menggunakan teknik observasi dan dianalisis dengan teknik statistik anova untuk menghitung frekuensi dan rata-rata hitung pretes dan postes baik kelas eksperimen maupun kelas kontrol. Hasil penelitian menunjukkan bahwa penggunaan buku dongeng sainsmatika mampu meningkatkan karakter bersahabat siswa secara signifikan.Keywords: dongeng, sainsmatika, karakter bersahabat